2016
DOI: 10.4314/jae.v20i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Rural Women’s Participation in the Growth Enhancement Support Scheme in Abia State Nigeria

Abstract: This work assessed the participation of rural women in the Growth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…This findings implies that community members always participated in conference organized by Shell Petroleum Development Company as part of their Global Memrandum of Understanding (GMoU) with host communities in their various clusters. This is in line with the work of Umeh (2018) who reported that youths participated in community physical infrastructural development projects and impact assessment studies. Source: Field survey data (2018)…”
Section: Results and Discussion Level Of Participation Of Community M...supporting
confidence: 91%
“…This findings implies that community members always participated in conference organized by Shell Petroleum Development Company as part of their Global Memrandum of Understanding (GMoU) with host communities in their various clusters. This is in line with the work of Umeh (2018) who reported that youths participated in community physical infrastructural development projects and impact assessment studies. Source: Field survey data (2018)…”
Section: Results and Discussion Level Of Participation Of Community M...supporting
confidence: 91%